Assessment of Impacts Produced by Anthropogenic Sources in a Little City near an Important Industrial Area (Modugno, Southern Italy) - Martino Amodio; Gianluigi de Gennaro; Annalisa Marzocca; Livia Trizio; Maria Tutino (The Scientific World Journal)
An annual monitoring campaign of VOCs, consisting of twelve sampling periods, was carried out from June 2008 to June 2009 in Modugno, a city located in the Apulia region (Southern Italy), in order to assess the urban air quality, identify the main emission sources, and quantify the cancer and no-cancer risk attributable to inhalation exposures. Monitoring, carried out by using the Radiello diffusive samplers, was conducted in eleven sampling sites throughout the city taking into account the traffic density and the architecture of the city. From the study of the data, it was found that, among all considered VOCs, benzene, toluene, ethylbenzene, and xylenes (BTEX) are the pollutants at higher concentration. The analysis of VOC concentrations, the study of the topography of the city, and the use of different diagnostic ratios between the BTEX species showed that the vehicular traffic emissions were the predominant source of VOCs in the urban area of Modugno. Despite that the annual concentration of benzene is lower than the regulatory limit, the estimation of cancer risk showed that the global lifetime cancer risk attributed to the investigated VOC exposure was not negligible and therefore should be taken into account in future regulatory approaches.